Analisis pengaruh pertumbuhan ekonomi, rata-rata lama sekolah, dan angka melek huruf terhadap angka kemiskinan di kota samarinda (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
This studied aims to determine the effect of economic growth, average length of schooling, and literacy rates on poverty rates in Samarinda City. The data used in this study were sourced from data published by the Badan Pusat Statistik of Samarinda City for the past ten years, from 2009 to 2018. These data were then analyzed using multiple linear regression and the effect of hypothesis testing using correlation analysis and test -t. All analytical calculations use the IBM SPSS Statistics 20. The results of the analysis obtained are: (1) Economic growth has a very weak correlation level and does not have significant effect on the poverty rate in Samarinda City. (2) The average length of school has a sufficient and influential but not significant correlation to the poverty rate in Samarinda City. (3) Literacy rate has a very weak and influential correlation level but it is not significant on poverty rates in Samarinda City.